Enhancing physics learning through the 7E learning cycle model: A systematic literature review - Musfiroh, Maryam; Suwarma, Irma Rahma; Efendi, Ridwan (Indonesian Journal of Science and Mathematics Education, 2024)
This study aims to explore the application of the 7E learning cycle model (Elicit, Engage, Explore, Explain, Elaborate, Evaluate, and Extend) in physics education to enhance learning effectiveness. The method employed is a systematic literature review, with articles sourced from the Scopus database. A total of 16 articles were selected through screening using the PRISMA protocol. The analysis results indicate that the 7E learning cycle model significantly improves various student skills, including science process skills, motivation, critical and creative thinking skills, self-efficacy, conceptual understanding, and scientific literacy. Popular topics discussed include temperature and heat, static fluids, work and energy, the solar system, and Earth's systems. Additionally, this model can be integrated with other teaching methods and innovative learning media to boost student interest and motivation. In conclusion, the 7E learning cycle model is an effective approach that contributes to enhancing the quality of physics education. This study's implications provide practical guidance for educators in applying the 7E learning cycle model.